The Effect of Metabolic Syndrome on the Outcome of Hepatitis B-Associated Hepatocellular Carcinoma Patients After Hepatectomy: A Multicenter Study - Dai, Junlong; Zhu, Xinrui; Shen, Junyi; Zhang, Yu; Xie, Fei; Yu, Yu; Jiang, Kangyi; Wen, Tianfu; Li, Chuan (Frontiers in Oncology, 2022)
Background & aims: With changes in dietary patterns and modern lifestyles, the prevalence of metabolic syndrome (MetS) in hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) patients is increasing. The purpose of our study was to clarify the impact of MetS on the prognosis of HBV-associated HCC patients following radical hepatectomy. Methods: Data on consecutive HCC patients who underwent radical hepatectomy were prospectively obtained and retrospectively analyzed from seven medical centers in west areas of China. A propensity score matching (PSM) analysis was conducted to categorize patients into MetS-HBV-HCC group and HBV-HCC group. Surgical outcomes have been contrasted between the two groups. Results: 179 patients (18.19%) were identified with MetS in 984 patients. Patients in the MetS-HBV-HCC group had higher CCI score (8.7 [0.0, 12.2] vs. 0.0 [0.0, 8.7], p = 0.048) and a higher rate of severe complications (Clavien-Dindo ≥ 3, 7.82% vs. 4.10%, p = 0.035), especially in postoperative liver failure, hydrothorax and hyperglycemia. Patients in the MetS-HBV-HCC group tended to have worse 5-year overall survival (OS) rate (61.45% vs. 69.94%, p = 0.027) and recurrence-free survival (RFS) rate (62.57% vs. 53.66%, p = 0.030), consistent with the results of the competing risk model models. Moreover, MetS was identified to be the independent unfavorable prognostic factors in the multivariate analysis. Conclusion: The involvement of MetS could increase the risk of postoperative complications and worsen the overall survival and recurrence-free survival time reminding us to pay more attention to metabolic disorder among tumor patients.